(3GdeNJUQ GdeMJGL Edjg ef JGQjN HZOGOs - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s; (3GHf GdOHjKj , eMeO Hf SYjO Hf jMji, CHh YHO Gddg GdYQGbj,J (B637 (3g` ? s
(3ChdgG (B:s
(3GdMeO ddg GdChd HdG EHJOGA GdBNQ HdG EfJgGA s
(3GdfSNI HgG MhGTs
(3HgGeTgG JbjjOGJs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B139 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B40s
Keywords: (3GdJGQjNs